Determination of the reduced electric field in surface dielectric barrier discharge plasmas - Mutalip, А.А.; Ussenov, Y.А.; Akildinova, А.K.; Dosbolayev, М.K.; Gabdullin, М.Т.; Ramazanov, Т.S. (KU Publ., 2021)
In this paper the experimental determination of the reduced electric field (E/n) in plasma of dielectric coplanar surface barrier discharge (DCSBD) at atmospheric pressure was demonstrated. The plasma characteristics and the experimental setup properties were described, and the optical emission spectrum of the plasma was also measured. The results of optical emission spectroscopy showed the presence of nitrogen molecular bands in the emission spectrum of DCSBD. In particular, the second positive and the first negative systems, as well as low intensity OH and NO lines were identified. The main transport properties of electrons, such as mobility, mean average energy, and diffusion coefficients were calculated using the BOLSIG+ open source software. The dependence of the ratio of intensities of the nitrogen spectral lines on the reduced electric field, the dependence of the E/n on plasma power, and the dependence of the electron energy distribution function (EEDF) on E/n were obtained. An algorithm in the form of a block diagram for determining the reduced electric field by the BOLSIG + program and experimentally measured spectral line intensities are presented. The utilized method are quite simple, accessible and versatile.
Диэлектрлік беттік тосқауылдық разрядтағы плазманың меншікті электр өрісін анықтау
Определение приведенного электрического поля в плазме диэлектрического поверхностного барьерного разряда
Keywords: plasma; dielectric barrier discharge; spectroscopy; reduced electric field; lines intensity; nitrogen spectrum; Boltzmann equation